2005
DOI: 10.5580/15cb
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Cultivation of Halophilic Archaea from Solar Salterns Located in Peninsular Coast of India

Abstract: Two brightly red-pigmented, motile, rod and triangular-shaped, extremely halophilic archaea were isolated from saltern crystallizer ponds located in peninsular coast of India. They grew optimally at salt concentrations between 25 and 35% and did not grow below 20% salts. Thus, these isolates are among the most halophilic organisms known within the domain Bacteria. The isolate HA3 showed optimal growth at 42°C whereas HA9 showed optimal growth at 52°C. These haloversatile microorganisms were presumed as new str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This is because halophiles show more or less wide ranges of growth at different salinities, but experience optimum growth at salinity significantly higher than sea water [19]. Studies on halophilic microorganisms isolated from ponds of China and Karak region showed their optimum growth at the temperature of 35°C to 40°C [20].…”
Section: Growth Characteristics Of Isolated Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because halophiles show more or less wide ranges of growth at different salinities, but experience optimum growth at salinity significantly higher than sea water [19]. Studies on halophilic microorganisms isolated from ponds of China and Karak region showed their optimum growth at the temperature of 35°C to 40°C [20].…”
Section: Growth Characteristics Of Isolated Strainmentioning
confidence: 99%
“…It was earlier thought that all extremely haloarchaea required a number of amino acids and no carbohydrates for their growth [19]. Halotolerant bacteria have wider metabolic activities so they use many carbon sources for growth [26].…”
Section: Growth In Various Carbon Sourcesmentioning
confidence: 99%